Analisis Faktor- Faktor Yang Mempengaruhi Penjualan Produk Impor Apparel Dengan Unsur Tactical Military (Studi Kasus Pada PT. Indo Taktika Gritama) - Tika Ayu Marsiani; Achsanul Nashir (JAMBIS : Jurnal Administrasi Bisnis, 2023)
Imported apparel products with tactical military elements are increasingly recognized by consumers in the Indonesian market. Consumers' interest in tactical dress styles can be seen in their appearance and daily activities. Fans of the tactical military style come from various circles, both TNI and Polri and civil society, with various backgrounds. This study aims to identify and analyze the factors that influence the sales of import apparel products with tactical military elements (case study of PT. Indo Taktika Gritama). In addition, this study was also conducted to identify and analyze the obstacles and solutions to the existing obstacles. The approach used is descriptive-analytical qualitative, with advantages in the form of the ability to numerically analyze difficult or unmeasured problems. This study uses data analysis techniques with the theory of Miles, Huberman and Saldana. The influencing factors include aspects of function, quality, innovation, technology, price, needs, social environment and ease of shopping